Image compression in all-optical domain using one 6×6 multimode interference coupler - Thuy, Bui Thi; Le Trung Thanh (Vietnam Journal of Science and Technology, 2023)
We present a new method for image compression using the Haar wavelet transform (HWT) in all-optical domain. The proposed architecture is based on the optical Haar wavelet transform using only one 6×6 multimode interference (MMI) coupler. By locating the positions of input and output waveguides and optimizing design length of the MMI, the expected matrix of the Haar transform is obtained. The new hardware architecture is suitable for directly integrating with digital cameras for image processing. The processing of images therefore is at very high speed. Our method can also be applied to data compression in big data analytics. Our structure can provide a large fabrication tolerance which is compatible with the CMOS existing technology. Our simulations show that the length variation of ± 2 µm still keeps the output powers unchanged. We have simulate successfully the use of the proposed HWT to compress cameraman image with the compressed ratios of 20, 30, 50 % with MSE and PSNR from 0.1 - 0.3 and 62 – 67 dB, respectively.